Full Stack Development with Angular and GraphQL : learn to build scalable monorepo and a complete Angular App Using Apollo, Lerna, and GraphQL. - Bouchefra, Ahmed (Packt Publishing, Limited, 2022)
Design and develop full-stack and cross-platform Angular applications using the latest web tooling, development techniques, and modern app architecture Key Features Implement scalability and maintainability to your full stack apps using Angular modules and components Get the complete source code of the example social network app built using GraphQL and Apollo Manage your Angular applications state using Apollo client for a seamless user experience Book DescriptionGraphQL is an alternative to traditional REST technology for querying Web APIs. Together with Angular and TypeScript, it provides a tech stack option for building future-proof web applications that are robust and maintainable at any scale. This book leverages the potential of cutting-edge technologies like GraphQL and Apollo and helps Angular developers add it to their stack. Starting with introducing full-stack development, you will learn to create a monorepo project with Lerna and NPM Workspaces. You will then learn to configure Node.js-based backend using GraphQL, Express, and Apollo Server. The book will demonstrate how to build professional-looking UIs with Angular Material. It will then show you how to create Web APIs for your frontend with GraphQL. All this in a step-by-step manner. The book covers advanced topics such as local state management, reactive variables, and generating TypeScript types using the GraphQL scheme to develop a scalable codebase. By the end of this book, you'll have the skills you need to be able to build your full-stack application. What you will learn Create a monorepo project with Lerna and NPM workspaces Add realtime support with GraphQL subscriptions Build a frontend with a modular architecture and Material Design UI components to consume the GraphQL API Use GraphQL Code Generator to generate types and code for a type-safe and scalable code base Create Angular modules and smart and dumb components and share data between them Use Apollo Client features such as client-side queries and reactive variables for local state management Who this book is for The book is aimed at Angular developers who wish to learn about GraphQL for taking their frontend knowledge in full stack web development. The book assumes intermediate knowledge of Angular, however, full stack development is not required.